5-HT2A receptor loss does not alter acute fluoxetine-induced anxiety and exhibit sex-dependent regulation of cortical immediate early gene expression. Issue 1 (1st February 2019) - Jaggar, Minal; Banerjee, Toshali; Weisstaub, Noelia; Gingrich, Jay A.
No abstract available